Data from: Synchrony is more than its top-down and climatic parts: interacting Moran effects on phytoplankton in British seas - Sheppard, Lawrence William; Defriez, Emma J.; Reid, Philip Christopher; Reuman, Daniel C. (Zenodo, 2019)
Large-scale spatial synchrony is ubiquitous in ecology. We examined 56 years of data representing chlorophyll density in 26 areas in British seas monitored by the Continuous Plankton Recorder survey. We used wavelet methods to disaggregate synchronous fluctuations by timescale and determine that drivers of synchrony include both biotic and abiotic variables. We tested these drivers for statistical significance by comparison with spatially synchronous surrogate data. We generated timescale-specific models, accounting for 61% of long-timescale (> 4yrs) synchrony in a chlorophyll density index, but only 3% of observed short-timescale (< 4yrs) synchrony. The dominant source of long-timescale chlorophyll synchrony was closely related to sea surface temperature, through a Moran effect, though likely via complex oceanographic mechanisms. The top-down action of Calanus finmarchicus predation enhances this environmental synchronising mechanism and interacts with it non-additively to produce more long-timescale synchrony than top-down and climatic drivers would produce independently. Thus we demonstrate interaction effects between Moran drivers of synchrony, a new mechanism for synchrony that may affect many ecosystems at large spatial scales. Plankton and oceanographic time-series This zip file includes annualized Plankton Colour Index time-series, annualized plankton species abundance time-series, and annualized oceanographic variables. See readme.txt file. planktontimeseries.zip Funding provided by: National Science Foundation Crossref Funder Registry ID: http://dx.doi.org/10.13039/100000001 Award Number: 1442595, 1714195